2011
DOI: 10.1007/s11726-011-0490-8
|View full text |Cite
|
Sign up to set email alerts
|

Research progress of electroacupuncture treatment on cervical spondylosis radiculopathy in recent ten years

Abstract: 【Abstract】Objective: To introduce electroacupuncture (EA) treatment on cervical spondylosis radiculopathy (CSR) at home and abroad in the prior ten years. Methods: EA, combined EA and other treatments for NCS are classified and analyzed. Results: The most commonly used acupoints are JiaJi (Ex-B2), Fengchi (GB 20), Waiguan (TE 5), Quchi (LI 11). EA is widely applied to treat CSR because of its definite therapeutic effects and safety. Conclusion: The validity of other evaluation indexes needs to be proved by mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Presently, although a variety of treatments are available for neck pain relief of CS, such as nonsteroidal anti-inflammatory drugs, [ 17 ] physiotherapy, [ 18 , 19 ] analgesics, [ 20 , 21 ] among others, those therapies have limited efficacy in relieving neck pain and many of them are associated with cumbersome side effects. It has been reported that alternative medicine, such as acupuncture, [ 22 ] neck exercise, [ 18 , 23 ] percutaneous neuromuscular electrical stimulation (PNMES), [ 24 ] herbal medication, [ 25 ] and so on, has been widely used to treat neck pain of CS, and with few adverse events (AEs), or even without AEs. However, no randomized controlled trials focused to explore the effectiveness and safety of PNMES for neck pain relief in patients with CS.…”
Section: Introductionmentioning
confidence: 99%
“…Presently, although a variety of treatments are available for neck pain relief of CS, such as nonsteroidal anti-inflammatory drugs, [ 17 ] physiotherapy, [ 18 , 19 ] analgesics, [ 20 , 21 ] among others, those therapies have limited efficacy in relieving neck pain and many of them are associated with cumbersome side effects. It has been reported that alternative medicine, such as acupuncture, [ 22 ] neck exercise, [ 18 , 23 ] percutaneous neuromuscular electrical stimulation (PNMES), [ 24 ] herbal medication, [ 25 ] and so on, has been widely used to treat neck pain of CS, and with few adverse events (AEs), or even without AEs. However, no randomized controlled trials focused to explore the effectiveness and safety of PNMES for neck pain relief in patients with CS.…”
Section: Introductionmentioning
confidence: 99%
“…However, all of them had unsatisfied efficacy and adverse events. Acupuncture therapy is used to treat various conditions, such as pain [15][16][17] (including neck pain [18,19], knee pain [20][21][22]), stroke rehabilitation [23], urinary dysfunction [24,25], pressure ulcers [26,27], and OP [28].…”
Section: Introductionmentioning
confidence: 99%
“…However, all of them had unsatisfied efficacy and adverse events. Acupuncture therapy is used to treat various conditions, such as pain [ 15 17 ] (including neck pain [ 18 , 19 ], knee pain [ 20 22 ]), stroke rehabilitation [ 23 ], urinary dysfunction [ 24 , 25 ], pressure ulcers [ 26 , 27 ], and OP [ 28 ].…”
Section: Introductionmentioning
confidence: 99%